The Importance of Understanding the Facts of Cases in Judicial Proceedings: An Analysis from Islamic Judicial Perspective (Kanun: Jurnal Undang-undang Malaysia, 2022)
The importance of understanding the factual reality (fiqh al-waqi‘)of a case has been extensively discussed by Muslim jurists in their deliberation of Islamic legal theory. It has been accepted as an important component of the practice of ijtihad and recognized as a valid justification for the renewal of ijtihad. In light of the above, yet in a different setting, this paper discusses the concept of al-da‘wa and the significance of understanding the fact of a legal dispute (fahm al-da‘wa) in Islamic judicial proceedings. It examines the significance of fahm al-da‘wa by the trial judge in judicial proceedings. This doctrinal research finds that understanding of facts of the cases assumes a very critical position in judicial proceedings, the laxity of which affect the propriety of judicial decisions and thus lead to injustice. Further, the paper argues that the kind of facts that need to be ascertained and understood by trial judges are not limited to the specific and direct facts of the cases, rather, the general circumstances and the reality of the living conditions of the times need consideration as well. Finally, the paper avers that the obligation to understand the facts of the cases necessitates a kind of undertaking in the nature of ijtihad which is to be carried out by all judges regardless of their status, whether they are mujtahid (jurist) or muqallid (imitator).Keywords: Understanding of Facts, Islamic Judicial Proceedings, facts of cases, al-da’wa, Judicial Ijtihad, judgesFull text: PDF